Small RNA drugs for prion disease: a new frontier. (October 2013) - Boese, Amrit S; Majer, Anna; Saba, Reuben; Booth, Stephanie A
<x xml:space="preserve">Abstract</x> Introduction: Prion diseases, also known as transmissible spongiform encephalopathies, are a group of neurodegenerative diseases that are invariably incurable. In fact, intense laboratory and clinical research have failed to discover effective treatments, to date, which delay the onset or progression of any neurodegenerative conditions, including those caused by infectious prions. It has become clear that profound changes in the brains of patients are evident long before clinical signs and it is at this stage that the disease is reversible and presents 'druggable' targets. However, research is beginning to uncover the molecular underpinnings involved in the early stages of disease pathogenesis. Targeting key genes and pathways using short non-coding RNA is a new avenue of exploratory research for the treatment of prion disease that holds much promise for the future. Areas covered: This article reviews the novel approach of using RNA-based drugs as a therapeutic opportunity for prion disease. Furthermore, it discusses the challenges that currently exist in the development of these therapies and highlights the future opportunities in this area. Expert opinion: Numerous challenges exist before this therapeutic option can be translated into effective treatments. First, the crucial genes and pathways targeted must be identified from the multitude of temporally and spatially altered genetic processes that occur during the disease. Second, patients must be before irreversible neuronal degeneration, that accompanies prion replication, has progressed. Finally, these small RNAs must be delivered to the affected region of the brain over long periods of time and without significant side effects.